Anti‐tumoural activity of the G‐quadruplex ligand pyridostatin against BRCA1/2‐deficient tumours. Issue 3 (2nd February 2022) - Groelly, Florian J; Porru, Manuela; Zimmer, Jutta; Benainous, Hugo; De Visser, Yanti; Kosova, Anastasiya A; Di Vito, Serena; Serra, Violeta; Ryan, Anderson; Leonetti, Carlo; Bruna, Alejandra; Biroccio, Annamaria; et al.
Abstract: The cells with compromised BRCA1 or BRCA2 (BRCA1/2) function accumulate stalled replication forks, which leads to replication‐associated DNA damage and genomic instability, a signature of BRCA1/2 ‐mutated tumours. Targeted therapies against BRCA1/2 ‐mutated tumours exploit this vulnerability by introducing additional DNA lesions. Because homologous recombination (HR) repair is abrogated in the absence of BRCA1 or BRCA2, these lesions are specifically lethal to tumour cells, but not to the healthy tissue. Ligands that bind and stabilise G‐quadruplexes (G4s) have recently emerged as a class of compounds that selectively eliminate the cells and tumours lacking BRCA1 or BRCA2. Pyridostatin is a small molecule that binds G4s and is specifically toxic to BRCA1/2‐deficient cells in vitro . However, its in vivo potential has not yet been evaluated. Here, we demonstrate that pyridostatin exhibits a high specific activity against BRCA1/2‐deficient tumours, including patient‐derived xenograft tumours that have acquired PARP inhibitor (PARPi) resistance. Mechanistically, we demonstrate that pyridostatin disrupts replication leading to DNA double‐stranded breaks (DSBs) that can be repaired in the absence of BRCA1/2 by canonical non‐homologous end joining (C‐NHEJ). Consistent with this, chemical inhibitors of DNA‐PKcs, a core component of C‐NHEJ kinase activity, act synergistically with pyridostatin in eliminating BRCA1/2‐deficient cells and tumours. Furthermore, we demonstrate that pyridostatin triggers cGAS/STING‐dependent innate immune responses when BRCA1 or BRCA2 is abrogated. Paclitaxel, a drug routinely used in cancer chemotherapy, potentiates the in vivo toxicity of pyridostatin. Overall, our results demonstrate that pyridostatin is a compound suitable for further therapeutic development, alone or in combination with paclitaxel and DNA‐PKcs inhibitors, for the benefit of cancer patients carrying BRCA1/2 mutations. Synopsis: DNA replication and repair defects caused by loss of BRCA1/2 can be exploited therapeutically to specifically target tumours carrying mutations in these genes. Pyridostatin and its combinations with NU‐7441 and/or paclitaxel, specifically eliminate BRCA1/2‐deficient tumours in vivo . Pyridostatin, a G‐quadruplex ligand, inflicts DNA damage and exhibits anti‐tumour activity in the absence of BRCA1/2 in vivo, including against patient‐derived PARPi‐resistant tumours. DNA lesions caused by pyridostatin are repaired by C‐NHEJ. Inhibition of C‐NHEJ with the DNA‐PK inhibitor NU‐7441 sustains unrepaired double‐strand breaks in BRCA1/2‐deficient cells, even after pyridostatin removal. Combination of pyridostatin with NU‐7441 and paclitaxel is associated with long‐lasting anti‐tumour efficacy in the absence of BRCA1/2. Pyridostatin and its combinations are well tolerated in vivo and pave the way for novel targeted anti‐tumour and/or maintenance therapies. Abstract : DNA replication and repair defects caused by loss of BRCA1/2 can be exploited therapeutically to specifically target tumours carrying mutations in these genes. Pyridostatin and its combinations with NU‐7441 and/or paclitaxel, specifically eliminate BRCA1/2‐deficient tumours in vivo .